Anti-Asian Racism and Racial Justice in the Classroom. (3rd April 2022) - Shin, Ryan; Bae, Jaehan; Song, Borim
Abstract : This article discusses the urgent issues and concerns about anti-Asian racism in our society and provides several pedagogical strategies to counter anti-Asian racism. We begin by discussing the history and context of anti-Asian racism in the US, from which we trace the historical origins and contexts of anti-Asian racism, violence, and stereotypes in popular culture and media. After that, we share several anti-Asian racism teaching strategies and practices, drawn from and influenced by the creative artworks of Asian contemporary artists such as Lisa Wool-Rim Sjöblom, Amanda Phingbodhipakkiya, and Monyee Chau, who demonstrate subverting racism against Asians during the COVID-19 global pandemic. Finally, after engaging our students in anti-Asian racism lessons, we share their art projects and written testimonials about anti-Asian racism. As a result, we strongly encourage educators to use, in their art curriculum, both history and contemporary artworks by artists to address anti-Asian racism and social justice.